Modeling the penetration of oscillating impulse electromagnetic fields through the screen, made of superconducting materials with time dispersion1 - V. T. Erofeenko; V. F. Bondarenko (Informatika)
A procedure of simulating the processes of impulse oscillating TE-polarized plane electromagnetic fields penetration through the superconducting thin-shelled plane screen is developed. The shielding boundary-value problem for Maxwell’s equations in the frame of Gorter – Kazimir model for superconducting materials with time dispersion is formulated. Two-sided boundary conditions connecting the electromagnetic fields on both sides of the screen are used. Impulse plane oscillating exponentially damped fields with millisecond and microsecond front time are considered as primary fields acting on the screen. The impulse field behind the screen is presented analytically in the integral form. A program for numerical investigation of impulses structure and their spectral composition depending on the temperature of the screen is developed. For quantitative estimation of shielding the coefficient of shielding efficiency, indicating how much impulse field weakens when passing through the screen, is calculated.